The Response of Late Season Cassava to Fertilizer Rates, Ratio and Timing of Application - Piya Duangpatra (Agriculture and Natural Resources, 1993)
A field experiment was conducted to investigate the impact of timing and rates of NPK fertilizer on growth and yield of 4 cassava varieties in sandy loam soil, Warin soil series. The results showed that cutting germination, fresh and dry weights of plant top and root, harvest index and starch content in root were varied with varieties and fertilizing treatments. On average, cassava responded markedly to rates of NPK fertilizers whereas the influence of split application at 2 different fertilizer ratios on growth and yield were not pronounced. For late season cassava, split application of NPK fertilizer equally at planting and at 7 months after planting had no advantage over non-split application (applied all fertilizer at 1 month after planting). This was also hold for fertilizer P ratio applied at planting in which higher P ratio exerted no beneficial effect over lower P ratio. It was apparent that fertilizing method normally recommend for wet season cassava (applied all fertilizer at 1 month after planting) seem to perform equally well for late season cassava.